Aspetti fenomenologici della spazializzazione dell’io nelle Operette morali - di Nardo, Martina (Rivista Internazionale di Studi Leopardiani, 2023)
The essay investigates the phenomenological foundations of spaces in which Operette’s characters actualize themselves, and how these foundations accord to the author’s Lebenswelt, hence to that relation between the self and the world that, leading to the modern subjectivism, is verified on a sensitive and sentimental level other than on a rational and scientific, especially Newtonian, one.